Deliberating our frames: how members of multi-stakeholder initiatives use shared frames to tackle within-frame conflicts over sustainability issues - Zimmermann, Angelika (Journal of business ethics, 2022)
Multi-stakeholder initiatives (MSIs) have been praised as vehicles for tackling complex sustainability issues, but their success relies on the reconciliation of stakeholders’ divergent perspectives. We yet lack a thorough understanding of the micro-level mechanisms by which stakeholders can deal with these differences. To develop such understanding, we examine what frames - i.e., mental schemata for making sense of the world-members of MSIs use during their discussions on sustainability questions and how these frames are deliberated through social interactions. Whilst prior framing research has focussed on between-frame conflicts, we offer a different perspective by examining how and under what conditions actors use shared frames to tackle ‘within-frame conflicts’ on views that stand in the way of joint decisions. Observations of a deliberative environmental valuation workshop and interviews in an MSI on the protection of peatlands - ecosystems that contribute to carbon retention on a global scale - demonstrated how the application and deliberation of shared frames during micro-level interactions resulted in increased salience, elaboration, and adjustment of shared frames. We interpret our findings to identify characteristics of deliberation mechanisms in the case of within-frame conflicts where shared frames dominate the discussions, and to delineate conditions for such dominance. Our findings contribute to an understanding of collaborations in MSIs and other organisational settings by demonstrating the utility of shared frames for dealing with conflicting views and suggesting how shared frames can be activated, fostered and strengthened.